Functional Photoacoustic Imaging of Gastric Acid Secretion Using pH‐Responsive Polyaniline Nanoprobes. Issue 34 (30th June 2016) - Li, Junwei; Xiao, Hong; Yoon, Soon Joon; Liu, Chengbo; Matsuura, Drew; Tai, Wanyi; Song, Liang; O'Donnell, Matthew; Cheng, Du; Gao, Xiaohu
Abstract : A stomach functional imaging technique based on photoacoustics achieves noninvasive gastric acid secretory assessment utilizing pH‐responsive polyaniline nanoprobes. A testing protocol mimicking clinical practice is established using a mouse model. After imaging, the nanoprobes are excreted outside the body without inducing systematic toxicity. Further optimization and translation of this technology can help alleviate patients' suffering and side effects.